Effect of roughness on journal bearing performance with non-newtonian fluids / K. Jagannath - Jagannath, K. (UiTM Press, 2010)
The present study investigates the effect of surface roughness properties on the steady-state and dynamic characteristics of hydro dynamic journal bearing using non-Newtonian lubricants obeying power-law model. An analytical expression for average film thickness is obtained and introduced in the modified Reynolds equation. The resulting differential equation is then solved by the finite difference method with a successive over-relaxation scheme. The modified Reynolds equation with rough surfaces having Gaussian distribution has been solved using the non-linear transient approach to determine the stability parameters considering longitudinal, transverse and isotropic roughness patterns. The equation of motion is then solved by the fourth-order Runge- Kutta method. The results are compared with established results for smooth bearings. It is found from the detailed analysis that roughness parameter considerably influences stability of journal bearings. Stability is highest when the bearing is rough than journal. Surface pattern orientation of bearings has an important role in determining the stable running of a bearing. Improvement in stability not only depends on whether the surfaces have isotropically, longitudinally, or transversely oriented surface but also on the variation in the roughness between journal and bearing. Transversely oriented surface with rough bearing gives higher stability. Lower L/D ratios (short bearing) gives better stability characteristics. Non-Newtonian effects cause the maximum film pressure to increase. It is observed from the pressure distribution that for different values of flow behavior index, non-Newtonian lubricants show flatter pressure distribution which is advantageous for bearings subjected to oscillatory loads.